2008
DOI: 10.1063/1.2978387
|View full text |Cite
|
Sign up to set email alerts
|

Enabling ab initio Hessian and frequency calculations of large molecules

Abstract: A linear scaling method, termed as cardinality guided molecular tailoring approach, is applied for the estimation of the Hessian matrix and frequency calculations of spatially extended molecules. The method is put to test on a number of molecular systems largely employing the Hartree-Fock and density functional theory for a variety of basis sets. To demonstrate its ability for correlated methods, we have also performed a few test calculations at the Moller-Plesset second order perturbation theory. A comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
93
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 36 publications
0
93
0
Order By: Relevance
“…In fact, in this work, Kohn prophesied that the DC-type methods would be applicable, within the following few years, to systems comprising of 10 3 to 10 5 atoms. Since 1994, Gadre and coworkers have independently developed the Molecular Tailoring Approach (MTA), [31][32][33][34][35][36] initially for molecular property evaluation and later for geometry optimization as well as Hessian calculation, along with its parallel implementation. MTA is based on DC-type of algorithm, which is built around a locally modified version of public domain ab initio quantum chemistry package GAMESS.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, in this work, Kohn prophesied that the DC-type methods would be applicable, within the following few years, to systems comprising of 10 3 to 10 5 atoms. Since 1994, Gadre and coworkers have independently developed the Molecular Tailoring Approach (MTA), [31][32][33][34][35][36] initially for molecular property evaluation and later for geometry optimization as well as Hessian calculation, along with its parallel implementation. MTA is based on DC-type of algorithm, which is built around a locally modified version of public domain ab initio quantum chemistry package GAMESS.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier benchmarks have showed that a scheme with minimum R g in range 3-4 Å , scaling factor less than 3 is generally good enough for reliable results for spatially extended molecules with minimal computational efforts. [32][33][34][35][36] Details of MTA, determination of R g value for atoms as well as for the scheme, correlation of R g with accuracy of the scheme, cardinality based equations for patching fragment-energies, etc., are discussed in detail in references. [34][35] After fragmentation, cardinality based expressions 34,35 for energy and gradients are set up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28] Some fragment based approaches [29][30][31][32][33][34][35][36][37][38][39][40] feature analytic second derivatives. [41][42][43][44][45][46] The fragment molecular orbital (FMO) method [47][48][49][50][51] is a fragment-based approach. In the FMO method, the system is divided into a set of fragments (also called monomers).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a large number of fragment-based methods [1][2][3][4][5][6][7][8][9][10] have been suggested in order to facilitate computing large systems with quantum-mechanical methods. The fragment molecular orbital ͑FMO͒ [11][12][13] method is based on dividing the system into pieces ͑fragments͒ and performing ab initio calculations on fragments, their pairs, and, optionally, triples.…”
Section: Introductionmentioning
confidence: 99%